Stressless sampling to improve diagnostics of catecholamine excess: new assay to determine metanephrines in saliva - Per M Thorsby; Sandra R Dahl; Tone Smetop; Tone Hæg Lindholm; Svetlana N Zykova (Endocrine Connections)
Determination of metanephrines in saliva has been reported as a pain- and hazard-free alternative to plasma-based tests with a potential to reduce false-positive results during diagnostic work-up for neuroendocrine tumours. No validated method has, however, been made available in the published literature so far. The aim of this work was to develop an LC-MS/MS method for the measurement of metanephrine, normetanephrine and 3-methoxytyramine in human saliva. As hyposalivation represents a real-life challenge in situations with catecholamine excess, special effort was made to minimise specimen volume and to make the assay suitable also for paediatric and geriatric populations. The method validation was performed according to relevant guidelines and included recovery from three different collection swabs (Salivette, SalivaBio and Salimetrics). Selectivity, interferences, matrix effects, limits of quantification, linearity of calibration, sample volume, trueness, within-run and total analytical repeatability, robustness, carry-over and stability were evaluated. A sample volume as low as 20 μL was acceptable for all analytes, but 50 μL sample volume gave lower LLOQ, higher accuracy and better precision. Total analytical variation was <15% and the minimum turnaround time was 3 h. Among the sample collection devices tested, highest recovery was achieved with SalivaBio (93–104%). Metanephrines were stable in saliva when stored at ambient temperature for 6 h, and tolerated at least 1 week of freezing at −20°C. The non-invasiveness, ease of specimen collection, better stability of analytes compared to plasma and analytical performance make the method relevant for both research and diagnostics of states with catecholamine excess.